Infection with soil-transmitted helminths and their impact on coinfections - Schlosser-Brandenburg, Josephine; Midha, Ankur; Mugo, Robert M.; Ndombi, Eric M.; Gachara, George; Njomo, Doris; Rausch, Sebastian; Hartmann, Susanne (Frontiers in Parasitology, 2023)
The most important soil-transmitted helminths (STHs) affecting humans are roundworms, whipworms, and hookworms, with a large proportion of the world's population infected with one or more of these intestinal parasites. On top of that, concurrent infections with several viruses, bacteria, protozoa, and other helminths such as trematodes are common in STH-endemic areas. STHs are potent immunomodulators, but knowledge about the effects of STH infection on the direction and extent of coinfections with other pathogens and vice versa is incomplete. By focusing on Kenya, a country where STH infections in humans are widespread, we provide an exemplary overview of the current prevalence of STH and co-occurring infections (e.g. with Human Immunodeficiency Virus, Plasmodium falciparum, Giardia duodenalis and Schistosoma mansoni). Using human data and complemented by experimental studies, we outline the immunomechanistic interactions of coinfections in both acutely STH transmigrated and chronically infected tissues, also highlighting their systemic nature. Depending on the coinfecting pathogen and immunological readout, STH infection may restrain, support, or even override the immune response to another pathogen. Furthermore, the timing of the particular infection and host susceptibility are decisive for the immunopathological consequences. Some examples demonstrated positive outcomes of STH coinfections, where the systemic effects of these helminths mitigate the damage caused by other pathogens. Nevertheless, the data available to date are rather unbalanced, as only a few studies have considered the effects of coinfection on the worm's life cycle and associated host immunity. These interactions are complex and depend largely on the context and biology of the coinfection, which can act in either direction, both to the benefit and detriment of the infected host.